2016
DOI: 10.1016/j.watres.2015.11.053
|View full text |Cite
|
Sign up to set email alerts
|

A highly efficient polyampholyte hydrogel sorbent based fixed-bed process for heavy metal removal in actual industrial effluent

Abstract: a b s t r a c tHigh sorption capacity, high sorption rate, and fast separation and regeneration for qualified sorbents used in removing heavy metals from wastewater are urgently needed. In this study, a polyampholyte hydrogel was well designed and prepared via a simple radical polymerization procedure. Due to the remarkable mechanical strength, the three-dimensional polyampholyte hydrogel could be fast separated, easily regenerated and highly reused. The sorption capacities were as high as 216.1 mg/g for Pb(II… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
92
2

Year Published

2016
2016
2024
2024

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 228 publications
(96 citation statements)
references
References 49 publications
(43 reference statements)
2
92
2
Order By: Relevance
“…However, when the MBA content is higher than 0.8%, the MBA will make the networks of hydrogel extremely dense and smooth The environmental conditions such as pH and ionic strength will have influences on the surface charge of adsorbent as well as the ionization degree and solubility of adsorbates, consequently influencing the removal efficiency of heavy metal ions. 2,[13][14] In order to evaluate the influence of environmental conditions on the adsorption of Pb 2+ and Cd 2+ by the P(AANa-co-AM)/GO hydrogel, a series of adsorption and Mg 2+ ) were carried out. The adsorption results of Pb 2+ and Cd 2+ by the P(AANa-co-AM)/GO hydrogel as a function of pH are present in Figure 4 1 2 3 4 5 6 7 8 9 10 11 12 13 14 15 16 17 18 19 20 21 22 23 24 25 26 27 28 29 30 31 32 33 34 35 36 37 38 39 40 41 42 43 44 45 46 47 48 49 50 51 52 53 54 55 56 57 58 59 60 This may be due to that the hydrated radius of Mg 2+ and Ca 2+ is smaller than that of Cd 2+ but larger than that of Pb 2+ .…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…However, when the MBA content is higher than 0.8%, the MBA will make the networks of hydrogel extremely dense and smooth The environmental conditions such as pH and ionic strength will have influences on the surface charge of adsorbent as well as the ionization degree and solubility of adsorbates, consequently influencing the removal efficiency of heavy metal ions. 2,[13][14] In order to evaluate the influence of environmental conditions on the adsorption of Pb 2+ and Cd 2+ by the P(AANa-co-AM)/GO hydrogel, a series of adsorption and Mg 2+ ) were carried out. The adsorption results of Pb 2+ and Cd 2+ by the P(AANa-co-AM)/GO hydrogel as a function of pH are present in Figure 4 1 2 3 4 5 6 7 8 9 10 11 12 13 14 15 16 17 18 19 20 21 22 23 24 25 26 27 28 29 30 31 32 33 34 35 36 37 38 39 40 41 42 43 44 45 46 47 48 49 50 51 52 53 54 55 56 57 58 59 60 This may be due to that the hydrated radius of Mg 2+ and Ca 2+ is smaller than that of Cd 2+ but larger than that of Pb 2+ .…”
Section: Resultsmentioning
confidence: 99%
“…Recently, various studies have found that hydrogel adsorbents exhibited super adsorption capacity, wide pH independence, easy regeneration and good reusability for removal of toxic metal ions and dyes from wastewater. [13][14][19][20][21][22] As a novel adsorbent, hydrogels are polymers with three dimensional (3-D) networks which can be formed via physical or chemical cross-linking using various water-soluble monomers 19,20,23 . Hydrogel adsorbents have attracted special attention in recent years for removing heavy metal ions due to the abundant functional groups and swollen polymeric networks of the polymer chain.…”
mentioning
confidence: 99%
“…The demand for new sorbents, which not only have a high surface area but which are also selective, continues to drive research into efficient and functionalized sorbent materials [31]. In a situation of growing environmental problems-global warming and water pollution, the breadth of potential applications is widening for these functionalized sorbents.…”
Section: Introductionmentioning
confidence: 99%
“…However, when the concentration of Pb 2+ exceeds 50 mM, the adsorption capacity of Alg-PAM remains stable and shows no further increase. Therefore, the maximum adsorption capacity of Alg-PAM for Pb 2+ is 252.2 mg/g, which is higher than that of most of the reported Pb 2+ sorbents (Table 2) [28][29][30][31][32][33][34][35][36][37][38][39][40][41].…”
Section: Adsorption Performance Of Alg-pam For Metal Ionsmentioning
confidence: 91%